@sologuitar

"Are you seeking help or teaching a mini lesson?"

Ha! Seeking help, always. And just as well, as I screwed up the final part of the answer. Good old amnkb to the rescue though.

This one was puzzling me for days. It was only after watching Maths Genie I realised you could expand brackets, factorise, etc when rearranging the subject.

I wonder what amnkb means?

]]>"Are you seeking help or teaching a mini lesson?"

Ha! Seeking help, always. And just as well, as I screwed up the final part of the answer. Good old amnkb to the rescue though.

This one was puzzling me for days. It was only after watching Maths Genie I realised you could expand brackets, factorise, etc when rearranging the subject.

]]>Make t the subject of the formula

p=(3-2t)/(4+t)

The left hand side was given in the traditional fraction form, with numerator on top of denominator; this is just the same, yeah, with the slash?

Here's my attempt;

Step 1

Mult.both sides by 4+t;

p(4+t)=3-2t

Step 2

Expand brackets;

4p+pt=3-2t

Step 3

Sub.4p from both sides;

pt=3-2t-4p

Step 4

Add 2t to both sides;

pt+2t=3-4p

Step 5

Factorise left side;

t(p+2)=3-4p

Step 6

Divide both sides by (p+2);

t=3-4p/p+2

Are you seeking help or teaching a mini lesson?

]]>Yes. Thanks.

“the part highlighted in your work is the tricky part

good for you for seeing it!”

Thanks. Maths Genie helped, as ever.

]]>Step 1

Mult.both sides by 4+t, assuming 4+t≠0

if 4+t=0 then original rational is undefined

so nonzero 4+t *is* assumed

Step 1

Mult.both sides by 4+t;

p(4+t)=3-2t

Step 1

Mult.both sides by 4+t, assuming 4+t≠0;

p(4+t)=3-2t

Make t the subject of the formula

p=(3-2t)/(4+t)

The left hand side was given in the traditional fraction form, with numerator on top of denominator; this is just the same, yeah, with the slash?

Here's my attempt;

Step 1

Mult.both sides by 4+t;

p(4+t)=3-2t

Step 2

Expand brackets;

4p+pt=3-2t

Step 3

Sub.4p from both sides;

pt=3-2t-4p

Step 4

Add 2t to both sides;

pt+2t=3-4p

Step 5

Factorise left side;

t(p+2)=3-4p

Step 6

Divide both sides by (p+2);

t=3-4p/p+2

grouping symbols are important!

't=3-4p/p+2' means this:

im pretty sure you mean 't = (3-4p)/(p+2)'

the part highlighted in your work is the tricky part

good for you for seeing it!

p=(3-2t)/(4+t)

The left hand side was given in the traditional fraction form, with numerator on top of denominator; this is just the same, yeah, with the slash?

Here's my attempt;

Step 1

Mult.both sides by 4+t;

p(4+t)=3-2t

Step 2

Expand brackets;

4p+pt=3-2t

Step 3

Sub.4p from both sides;

pt=3-2t-4p

Step 4

Add 2t to both sides;

pt+2t=3-4p

Step 5

Factorise left side;

t(p+2)=3-4p

Step 6

Divide both sides by (p+2);

t=3-4p/p+2